The impact of social activities on mental health among older adults in China - Gao, Duanyang; Li, Rui; Yang, Yuying (Frontiers in Public Health, 2024)
Background: Understand the current situation of social activities among older adults and its impact on mental health, providing policy basis and intervention measures to improve the mental health of the elderly.Collect relevant data from 8181 older adults aged ≥ 60 years old from the 2020 China Health and Retirement Longitudinal Study (CHARLS), constructing an analysis framework for social activities of older adults in China from three aspects: participation in social activities, number of social activities, frequency of social activities, and describe them, then analyzing the impact of social activities on their mental health using OLS and 2SLS regression models.This study also discusses the impact of eight social activities on the mental health of elderly people through subgroup.Result: Among 8181 older adults aged 60 and above, 3808 participated in social activities(56.24%), average number of social activities is 0.71, and average frequency of social activities is 1.31 times.The average score of mental health level measured by CES-D is 15.24 points. Participate in social activities can reduce the depression level of the elderly (β＝-0.352, 95%CI: -0.547 -0.158); the more social activities the elderly participate in, the lower the depression level of the elderly (β＝-0.214, 95%CI: -0.313 -0.115); the higher the frequency of participating in social activities, the lower the depression level of the elderly (β＝-0.133, 95%CI: -0.182 -0.083). In summary, social activities can improve the mental health level of the elderly adults in China. As for different types of social activities, visiting and socializing with friends, participating in club organization activities, playing mahjong, chess, cards, or going to community activity rooms and attending school or training courses can improve the mental health of the elderly.Discussion: The social activities in three dimensions among older adults in China need to be further improved, and participating in social activities can help improve their mental health. The conclusion provides important policy implications for encouraging and supporting older adults to participate in various social activities, increasing the number and frequency of elderly social activities, then help improving the mental health level of older adults.